Human-computer interaction. theory, design, development and practice : 18th International Conference, HCI International 2016, Toronto, ON, Canada, July 17-22, 2016. Proceedings /: theory, design, development and practice : 18th International Conference, HCI International 2016, Toronto, ON, Canada, July 17-22, 2016. Proceedings. Part I : (2016) - Unknown
No abstract available